Saṅketaṭīkā = Vāmadhvaja's Saṅketa commentary on Udayanācārya's Nyāyakusumāñjali - Vāmeśvaradhvaja ca. 2. H. 12. Jh. (L. D. series / Lalbhai Dalpatbhai Institute of Indology, 2013)
Treatise, with commentary, on the basic tenets of the Nyaya school in Hindu philosophy